Histone Deacetylase Inhibitor (HDACi) Suberoylanilide Hydroxamic Acid (SAHA)-mediated Correction of α1-Antitrypsin Deficiency - Bouchecareilh, Marion (American Society for Biochemistry and Molecular Biology, 2012)
α1-Antitrypsin (α1AT) deficiency (α1ATD) is a consequence of defective folding, trafficking, and secretion of α1AT in response to a defect in its interaction with the endoplasmic reticulum proteostasis machineries. The most common and severe form of α1ATD is caused by the Z-variant and is characterized by the accumulation of α1AT polymers in the endoplasmic reticulum of the liver leading to a severe reduction (>85%) of α1AT in the serum and its anti-protease activity in the lung. In this organ α1AT is critical for ensuring tissue integrity by inhibiting neutrophil elastase, a protease that degrades elastin. Given the limited therapeutic options in α1ATD, a more detailed understanding of the folding and trafficking biology governing α1AT biogenesis and its response to small molecule regulators is required. Herein we report the correction of Z-α1AT secretion in response to treatment with the histone deacetylase (HDAC) inhibitor suberoylanilide hydroxamic acid (SAHA), acting in part through HDAC7 silencing and involving a calnexin-sensitive mechanism. SAHA-mediated correction restores Z-α1AT secretion and serpin activity to a level 50% that observed for wild-type α1AT. These data suggest that HDAC activity can influence Z-α1AT protein traffic and that SAHA may represent a potential therapeutic approach for α1ATD and other protein misfolding diseases.